TINJAUAN FAKTOR YANG MEMPENGARUHI KUALITAS AIR PADA SISTEM RAIN WATER HARVESTING (RWH) - Yushananta, Prayudhy (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2021)
The increase in population due to the birth rate has put pressure on meeting the water needs of the people. In 2050, the global demand for clean water is to meet the needs of 9.7 billion people. One of the strategies developed for sustainable water use is rainwater harvesting (RWH). From many reports, the RWH system can meet household water needs. However, it needs special attention from the quality aspect due to pollution. This paper presents the factors affecting water quality in the RWH system through three stages. The first stage is when rainfall clears pollutants in the air. In the second stage, the rain removes dirt and particles in the catchment areaâ€”the third, flushing dirt on pipes and storage tanks. Maintenance must be done to all parts of the RWH system periodically and must be treated and disinfection before being used as drinking water.Â